Validity of the distinction between primary and secondary substance use disorder in patients with bipolar disorder: data from the first 1000 STEP-BD participants. - Fossey, MD; Otto, M; Yates, W; Wisniewski, SR; Gyulai, L; Allen, M; Miklowitz, D; Coon, K; Ostacher, M; Neel, J; Thase, M; Sachs, G; et al. (2006)
The validity of a primary/secondary substance use disorder (SUD) distinction was evaluated in the first 1000 patients enrolled in the Systematic Treatment Enhancement Program for Bipolar Disorder. Patients with primary SUD (n = 116) were compared with those with secondary SUD (n = 275) on clinical course variables. Patients with secondary SUD had fewer days of euthymia, more episodes of mania and depression, and a greater history of suicide attempts. These findings were fully explained by variations in age of onset of bipolar disorder. The order of onset of SUDs was not linked to bipolar outcomes when age of onset of bipolar disorder was statistically controlled. The primary/secondary distinction for SUD is not valid when variations in the age of onset of the non-SUD are linked to course characteristics.